Y-Site Compatibility Studies of Ketoprofen with Parenteral Nutrition Admixtures for Central and Peripheral Administration - Katarzyna Dettlaff; Aleksandra Gostyńska; Natalia Ziółkowska; Maciej Stawny (MDPI AG, 2022)
Ketoprofen (KTF) is often used in hospital wards, especially in its intravenous form. According to the literature review, the compatibility of ketoprofen with parenteral nutrition (PN) admixtures has not yet been investigated. For this reason, we aimed to provide data contributing to physical compatibility to ensure the safe co-administration of these medications. In this study, we examined the compatibility of KTF with eight selected commercial PN admixtures intended for central (Lipoflex Special, Omegaflex Special, Kabiven, SmofKabiven) and peripheral (Lipoflex peri, Omegaflex peri, Kabiven Peripheral, Olimel Peri N4E) administration. The KTF solution for infusion was combined in three different volume ratios with studied PN admixtures reflecting the conditions in clinical practice. The evaluation of undesirable physical destabilization of oil-in-water system or precipitate formation involved the visual inspection and the determination of mean droplet diameter, zeta potential, pH, and turbidity changes. The results of compatibility of KTF with eight commercial PN admixtures showed that three of them: Kabiven, SmofKabiven, and Kabiven Peripheral, are incompatible with KTF and should not be concomitantly administered.